Knowledge, attitude, intention, and program implementation of iron supplementation among adolescent girls in Sidoarjo, Indonesia - Hanna T. Hasianna Silitonga; Lutfi A. Salim; Ira Nurmala; Rachmat Hargono; Septiana Purwandini (AOSIS, 2023)
Background: The government established an iron supplementation program as a solution to overcome anemia in adolescent girls in Indonesia. Research shows that various factors influence the compliance of adolescent girls in consuming iron supplements, including knowledge, attitude, intention, and program implementation. Objective: This study aims to determine adolescent girls' knowledge, attitudes, and intentions and explore the program implementation of iron supplementation in high school adolescent girls in Sidoarjo, Indonesia. Materials and Methods: This was mixed-method research. Quantitative data was collected on 202 girls students from 3 high schools in Sidoarjo using a questionnaire.Qualitative data was collected by interviewing 13 high school girls from 3 schools in Sidoarjo and Focus Group Discussion with the health office and primary health center representatives in Sidoarjo. Results: Most adolescent girls' knowledge about anemia was still poor (59.9%), but knowledge about iron supplements was mostly good (59.9%). The attitudes towards anemia and iron supplements and intentions to consume iron supplements in adolescent girls were mostly low (51.0% and 51.5%). The focus group discussion found that the program was already referred to national guidelines, but the pandemic affected the implementation. Findings from the interview with adolescent girls show that the distribution of iron supplements in schools was carried out in 3 ways: distributed with explanations, distributed without explanation, and distributed only to students who request it or feel anemic. Conclusion: There is a need to improve the knowledge, attitudes, and intentions of adolescent girls and improve the implementation of iron supplementation programs in schools in Sidoarjo, Indonesia.